Administrative Accountability of the Government of Indonesia in Environmental Management for Tourism Development - Leonito Ribeiro; I Nyoman Gede Sugiartha (Community Service Journal of Law, 2022)
A good and healthy environment is a human right of every Indonesian citizen as mandated in Chapter 28H of the 1945 Constitution of the Republic of Indonesia. Unwise environmental management contributes to aggravating the decline in the quality of the environment, therefore it is necessary to increase environmental protection and management. The government's responsibility in protecting and managing the environment is a function of public services, to ensure that all residents have a good and healthy environment. So in development and so as not to damage the environment, the government fosters tourism business actors to comply with applicable regulations. Because if there is environmental damage, the government can be held accountable administratively, when the government neglects to carry out its obligations that are not in accordance with the aspirations of the community. This research is qualified as a normative and empirical legal research, by applying several types of approaches, namely, a statutory approach, a conceptual approach, a philosophical approach, a historical approach, a comparative approach, a case approach, including a cultural approach based on local community wisdom.The results of the study show that environmental protection and management is an effort to carry out very difficult, resulting in a decrease in the quality of the environment that is increasingly real. Therefore, the enforcement of administrative law is a real first step from the government to enforce the rule of law quickly for the protection of the environment. Administrative law enforcement, integrating the values ​​that develop in society in protecting and protecting the environment is an ideal form to protect and manage the environment wisely to realize development.If the government fails to protect and manage the environment in tourism development, the government can be held accountable administratively.